N -arachidonoyl l -serine, an endocannabinoid-like brain constituent with vasodilatory properties - Garry Milman; Yehoshua Maor; Saleh Abu‐Lafi; Michal Horowitz; Ruth Gallily; Sándor Bátkai; Fong-Ming Mo; László Offertáler; Pál Pacher; George Kunos; Raphael Mechoulam (2006)
The endocannabinoid N-arachidonoyl ethanolamine (anandamide), found both in the CNS and in the periphery, plays a role in numerous physiological systems. One might expect that the chemically related N-arachidonoyl-L-serine (ARA-S) could also be formed alongside anandamide. We have now isolated ARA-S from bovine brain and elucidated its structure by comparison with synthetic ARA-S. Contrary to anandamide, ARA-S binds very weakly to cannabinoid CB1 and CB2 or vanilloid TRPV1 (transient receptor potential vanilloid 1) receptors. However, it produces endothelium-dependent vasodilation of rat isolated mesenteric arteries and abdominal aorta and stimulates phosphorylation of p44/42 mitogen-activated protein (MAP) kinase and protein kinase B/Akt in cultured endothelial cells. ARA-S also suppresses LPS-induced formation of TNF-alpha in a murine macrophage cell line and in wild-type mice, as well as in mice deficient in CB1 or CB2 receptors. Many of these effects parallel those reported for abnormal cannabidiol (Abn-CBD), a synthetic agonist of a putative novel cannabinoid-type receptor. Hence, ARA-S may represent an endogenous agonist for this receptor.